2022
DOI: 10.1186/s12876-022-02154-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastric polyps: a 10-year analysis of 18,496 upper endoscopies

Abstract: Background/aims Gastric polyps (GPs) are usually asymptomatic lesions of the upper gastrointestinal tract observed in 1–3% of esophagogastroduodenoscopies (EGD). Most GPs are benign. The aim of this study was to precise the frequency of different types of gastric polyps in our population, and to analyze their possible association with other factors. Materials and methods A total of 18,496 consecutive patients undergoing EGD over a 10-year period (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
(36 reference statements)
0
14
0
1
Order By: Relevance
“…15 The median age of patients with gastric polyp in our study was 57 years old, this finding was in line with study by Yacoub et al which found the mean age of 58.1 years old. 16 Study by Jeong et al in South Korea, also found that the median age of FGP patients was 54 years old and for hyperplastic polyp was 58 years old. 17 We found that older patients was significantly associated with more prevalent of gastric polyp, this finding is supported by Park et al 18 Therefore, older age may become risk factor of gastric polyp.…”
Section: Discussionmentioning
confidence: 91%
“…15 The median age of patients with gastric polyp in our study was 57 years old, this finding was in line with study by Yacoub et al which found the mean age of 58.1 years old. 16 Study by Jeong et al in South Korea, also found that the median age of FGP patients was 54 years old and for hyperplastic polyp was 58 years old. 17 We found that older patients was significantly associated with more prevalent of gastric polyp, this finding is supported by Park et al 18 Therefore, older age may become risk factor of gastric polyp.…”
Section: Discussionmentioning
confidence: 91%
“…Gastric polyps are common abnormal findings in up to 2-7% of upper gastrointestinal endoscopies, and fundic gland polyps (FGPs) and hyperplastic polyps are the main abnormalities identified, with broad variability worldwide [1][2][3][4][5]. Changes occur in gastric polyps over time, with the proportion of FGPs becoming predominant and hyperplastic and adenomatous polyps decreasing in number [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most gastric polyps are benign (>85% of cases). The risk of malignancy or malignant transformation of gastric polyps depends on their histological structure (7). Due to the increased incidence of gastric neoplasia, encountering a polyp in the stomach during endoscopy causes concern in regard to malignant potential.…”
Section: Introductionmentioning
confidence: 99%